Analisis Manajemen Pengawasan Dan Evaluasi Pada Program Bahasa Arab Di Pondok Pesantren - Asbarin, Asbarin; Mulyanti, Titi; Jamil, Husnaini; Hervina H, Lola (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
The purpose of this study was to describe the type of supervision and conformity of the dimensions of George R. Terry’s standard of supervision and evaluation to the Arabic language activity program at MTs Al-Irsyad Tengaran 7 Batu city. The research method used is descriptive qualitative research. The source of the data is the results of interviews with the supervisor, the language department and the administrator of the Arabic language activity program. Data collection techniques using observation techniques, interviews, and documentation. Data analysis used Miles and Huberman analysis, which consisted of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the type of Arabic language activity program at MTs Al-Irsyad Tengaran 7 Batu city is a type of internal, preventive, repressive and passive supervision. The management of supervision and evaluation of Arabic program activities is in accordance with the standard dimensions of George Robert Terry’s supervisory management, namely: Standards, Measurements, Comparison, and Action. The researchers hope that this research can contribute to the development of Arabic language program management science and be able to construct Arabic language activity programs in order to get more comprehensive results.